Effects of high salinity and the exogenous application of an osmolyte on growth, photosynthesis, and mineral composition in two ornamental shrubs. Issue 1 (2nd January 2016) - Cirillo, C.; Rouphael, Y.; Caputo, R.; Raimondi, G.; Sifola, M. I.; De Pascale, S.
ABSTRACT: A greenhouse experiment was carried out to determine the growth, photosynthetic activity, and mineral composition in two ornamental shrubs [ Viburnum lucidum L. (arrow-wood) and Callistemon citrinus (Curtis) Stapf. (red bottlebrush)] that had been treated or not treated with 2.5 mM glycine betaine (GB) or 5.0 mM proline (Pro). Plants were supplied with a non-salinised or salinised nutrient solution containing 200 mM NaCl. Salinity caused reductions in plant growth parameters, shoot biomass production, and net CO2 assimilation in both species. Neither Pro nor GB were able to mitigate the adverse effects of salinity in bottlebrush, whereas GB reduced the deleterious effects of salt stress on arrow-wood, indicating a differential species-specific response to these osmolytes. The application of GB to salt-stressed arrow-wood increased apical and lateral shoot lengths, the number of leaves per plant, and shoot dry biomass by 222%, 113%, 238%, and 49%, respectively, compared to untreated or Pro-treated plants. The improved performance of salt-stressed arrow-wood plants whose roots were treated with 2.5 mM GB was attributed to partial suppression of Na uptake, higher chlorophyll concentrations, and the better nutritional status (higher K) of shoots.